Total Hip Bone Mineral Density as an Indicator of Fracture Risk in Bisphosphonate‐Treated Patients in a Real‐World Setting. (21st October 2021) - Banefelt, Jonas; Timoshanko, Jen; Söreskog, Emma; Ortsäter, Gustaf; Moayyeri, Alireza; Åkesson, Kristina E.; Spångéus, Anna; Libanati, Cesar
ABSTRACT: Bone mineral density (BMD) is an established measure used to diagnose patients with osteoporosis. In clinical trials, change in BMD has been shown to provide a reliable estimate of fracture risk reduction, and achieved BMD T ‐score has been shown to reflect the near‐term risk of fracture. We aimed to test the association between BMD T ‐score and fracture risk in patients treated for osteoporosis in a real‐world setting. This retrospective, observational cohort study included Swedish females aged ≥55 years who had a total hip BMD measurement at one of three participating clinics. Patients were separated into two cohorts: bisphosphonate‐treated and bisphosphonate‐naïve prior to BMD measurement, stratified by age and prior nonvertebral fracture status. The primary outcome was cumulative incidence of clinical fractures within 24 months of BMD measurement, with other fracture types included as secondary outcomes. Associations between T ‐score and fracture risk were estimated using proportional hazards regression and restricted cubic splines. A total of 15, 395 patients were analyzed: 11, 973 bisphosphonate‐naïve and 3422 bisphosphonate‐treated. In the 24 months following BMD measurement, 6.3% (95% confidence interval [CI], 5.9–6.7) of bisphosphonate‐naïve and 8.4% (95% CI, 7.5–9.4) of bisphosphonate‐treated patients experienced a clinical fracture. Strong inverse relationships between BMD T ‐score and fracture incidence were observed in both cohorts. Among bisphosphonate‐naïve patients, this relationship appeared to plateau around T ‐score −1.5, indicating smaller marginal reductions in fracture risk above this value; bisphosphonate‐treated patients showed a more consistent marginal change in fracture risk across the evaluated T ‐scores (−3.0 to –0.5). Trends remained robust regardless of age and prior fracture status. This real‐world demonstration of a BMD–fracture risk association in both bisphosphonate‐naïve and bisphosphonate‐treated patients extends evidence from clinical trials and recent meta‐regressions supporting the suitability of total hip BMD as a meaningful outcome for the clinical management of patients with osteoporosis. © 2021 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).